Characteristics of chicken production systems in rural Burkina Faso: A focus on One Health related practices and food security - Michel Dione; Guy Ilboudo; Abdoul Aziz Ouedraogo; Sidonie Aristide Ima; Brice Ouedraogo; Theodore Knight-Jones; Assèta Kagambèga; Robyn Alders (PLoS ONE, 2025)
In addition to having cultural importance, village chicken production remains an important source of cash income for most rural households in Burkina Faso. However, strict biosecurity and good management of chicken flocks are required to reduce the risk of exposure of communities to chicken waste at household level. We characterized village production systems in rural Burkina Faso in relation to importance to food security, biosecurity, husbandry and chicken health management. We surveyed 483 chicken-producing households and carried out 20 focus group discussions separately with men and women chicken producers in Boussouma commune, a typical rural setting. Crop farming was reported as the main income-generating activity carried out by chicken producers (79.5%). Seveny six per cent of households sold chicken to local markets. Chicken production and sales were aligned to social/cultural events (religious festivals, weddings, etc…) and school-fee payment period. While men spent more revenues from chicken production on agriculture and household equipment’s, women spent more on food, education and medical expenses. The chicken management system is mainly extensive scavenging, with most farmers (81.4%) keeping 5 to 50 birds with little or no supplementary feeding and rudimentary housing. Most producers indicated that Newcastle disease was the main cause of chicken mortality. While men consider high disease burden, lack of finance, and poor chicken housing as the major constraints, women prioritized the lack of adequate chicken housing, lack of feeds and limited access to veterinary services. With locally adapted interventions that build one a One Health approach, village chicken keeping has the potential to secure and greatly improve smallholder livelihoods and household food security, while preserving public health in Burkina Faso.